NGOs ʻĪsān : thānl̄ưak h̄æng phalang kānplīanpl̄æng (Khana Kammakān Prasān Ngān ʻOngk̨̄on ʻĒkkachon Phatthanā Chonnabot Phāk ʻĪsān, 1997)
Non-government organization, selected path of Isan, Northeastern Thailand for socio-economic development.